Muscle strength in different phases of menstrual cycle in context of theoretical analysis - Leal Cortes, A. K.; Ferreira, A. K.; Alves, P. S.; Martin Dantas, E. E.; Gomes, A. K.; Fomichenko, T. G. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to theoretically analyze the women`s muscle strength and physical working capacity variations with the menstrual cycle phases.